ضوابط الاستدلال بالقواعد الفقهية على النَّوازل المعاصرة زرع الأعضاء أنموذجا - تومي, نور الدين (جامعة الوادي - University of Eloued, 2019)
يسلط هذا البحث الضوء على دور القواعد الفقهية في حلِّ المستجدات والنَّوازل المعاصرة، وقد تناول مسألة زرع الأعضاء أنموذجا من تلك النّوازل لإبراز هذا الدور المهم، حيث تطرق البحث أولا إلى الاستدلال بالقواعد الفقهية من حيث العموم، ثم الاستدلال بها على النّوازل، وبعد ذلك تناول البحث القواعد الفقهية المستدل بها على زرع الأعضاء؛ فَذُكِرتْ القواعد التّي استدل بها المجيزون والمانعون، ثم ختم البحث بذكر ضوابط الاستدلال بالقواعد الفقهية على جواز زرع الأعضاء. This research highlights the role of fiqh rules in resolving contemporary developments and nawazel, and has dealt with the issue of organ transplantation from this nawazel to highlight this important role. The research first dealt with inference the fiqh rules in terms of general, then to inference the rules on the nawazel, and then the research dealt with the fiqh rules related to organ transplantation between supporters and opponents. Then he concluded the research by mentioning the regulations for inference on t the fiqh rules the permissibility of organ transplantation.
مقال
Keywords: ضوابط؛ الاستدلال؛ القواعد الفقهية؛ النوزال؛ زرع الأعضاء; regulations; inference; The fiqh rules; Nawazel; organ